Advances on the Development of Microfluidic Paper-based Analytical Device for Detection of Salivary Glucose - Santana-Jiménez, L. A.; Márquez-Lucero, A.; Domínguez, R. B. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2017)
The people living with Diabetes Mellitus (DM) has considerably increased over the last decades, becoming a major health problem for most countries. The frequent monitoring of blood samples is essential, but the available current technology is based on invasive sample collection, which can discourage the monitoring and lead to poor management of the disease. In this work we present the advances of the development of a Microfluidic Paper-based Analytical Devices (μPAD) for monitoring of DM through salivary samples. The low-cost device was created by transferring a hydrophobic material over a Whatman filter paper in a designed pattern with a stamping process. Obtained patterns were modified with chitosan in order to create a biocompatible environment for immobilization of glucose oxidase-peroxidase byenzimatic system. Two chomopheres were tested in order to achieve the high sensibility required for detection of glucose in salivary samples. The resulted μPADs were evaluated with stock glucose samples and real salivary samples showing a distinctive color change. The results suggest the developed devices can be optimized and applied as low-cost, easy to use and non-invasive test for DM monitoring.